MIOSITIS BADAN INKLUSI - Sri Yenni Trisnawati, Anak Agung Bagus Ngurah Nuartha, IGusti Ngurah Purna Putra (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION INCLUSION BODY MYOSITIS IBM WAS PART OF THE INFLAMMATORY MYOPATHIES IM WHICH THE ANNUAL INCIDENCE OF AROUND 210 NEW CASES PER 1 MILLION PEOPLE IBM WAS A PROGRESIVE INFLAMATORY DISEASE OF THE MUSCLE WITH AN UNKNOWN CAUSE FROM CLINICAL APPEARANCE IT WAS DIFFICULT TO DIFFERENTIATEFROM OTHER IM DISEASE SUCH AS POLYMYOSITIS PM AND DERMATOMYOSITIS DM UNTIL MUSCLE BIOPSY IS NECESSARY AS A GOLD STANDARD DIAGNOSTIC METHOD IBM HAS TO BE DIFFERENTIATED FROM PM AND DM BECAUSE IBM HAS NO RESPONSE TOWARDS STEROID IMMUNOSUPPRESSANT AND IMMUNOMODULATORY